Does Education Affect Rural Women’s Trust? Evidence From China - Xu, Siyu; Zhao, Yeye; Aziz, Noshaba; He, Jun (Frontiers in Psychology, 2022)
Trust is great significance to the economic and social development of a country. The trust of rural women in China has undergone tremendous changes along with the development of rural areas. It is seen that the trust of rural women has changed from localized to generalized trust, and it is stated that the major factor leading to this transformation is education. To explore this phenomenon empirically, the current study uses the survey data of rural women sourced from China Family Panel Studies (CFPS) over the year 2018. Through the ordered probit model, the study reveal that education has a positive and significant effects on both generalized trust and localized trust. The study further reveals the influence mechanism that information flows, access to public resources, and income mediate the relationship between education and generalized trust. Besides, the outcomes unveil that the impact of education on localized trust is stronger when the level of mobility is low. The study employs a regression discontinuity model to do the robustness test. Based on the current findings, the study suggests that the major factor leading to trigger the trust of rural women in China is education, so the policymakers in China should imply education-oriented strategies as individuals with higher levels of education are more inclined to trust.